British geography 1918-1945 (Cambridge Univ, 1987)
The book traces the foundations of modern British geography based upon the first-hand recollections of some of those active in the discipline between the wars and after. It discusses not only the growth of geography as a specific academic discipline but also the relationship between geography and national planning that played such an important role in post-war reconstruction